المعارض عبر الانترنت ومدى اتاحتها على مواقع المکتبات الوطنية - وسام الزغبى (المجلة الدولية لعلوم المكتبات والمعلومات)
Exhibitions play a vital role in spreading knowledge by basic memoryinstitutions (libraries - archives - museums), but traditional exhibitions faceproblems or restrictions, the most important of which are space and size, andthey may also encounter problems that require their elimination or postponementof some emergency circumstances such as wars and epidemics, as happened inthe last time due to the spread of the Corona virus, which led officials to the ideaof finding replacements to traditional exhibitions, as ideas turned towards onlineexhibitions.From here, the problem of this study crystallized around knowing theconcept of online exhibitions (electronic / virtual), identifying the advantages theyoffer and the defects related to them, studying the characteristics of thoseexhibitions and design steps, in addition to studying the availability of theseexhibitions on the websites of national libraries.The study relied on the descriptive analytical method to achieve itsobjectives depending on the search engines to restrict the society of the study,which restricted the number (222) national libraries all over the world, (73)national libraries were excluded because they do not have a website or only havea page on Facebook , the number of national libraries under study that have awebsite on the Internet has become (149) national libraries, as the study hasproven the existence of (40) national library sites that hold electronic or virtualexhibitions, by 27% from total libraries under study which are (149) NationalLibraries.